KOORDINASI PEMERINTAH DAERAH DENGAN LEMBAGA ADAT DALAM PELESTARIAN HUTAN ADAT DI KAWASAN ADAT AMMATOA KAJANG KABUPATEN BULUKUMBA - Faisal Faisal; Andi Nuraeni Aksa; Muh Ahsan Samad (Otoritas : Jurnal Ilmu Pemerintahan, 2012)
The purpose of this study was to determine how the coordination between the Institute of Traditional and Local Government in terms of preservation of Indigenous Traditional Forest Region Ammatoa Kajang Kajang Subdistrict Bulukumba. This type of research is qualitative. The data was analyzed by descriptive qualitative. The results showed that the coordination between the local government with customary institutions in preserving indigenous forests in the area of customs Ammatoa Kajang Bulukumba going well although not maximized. Coordination problems in the indigenous forest conservation Ammatoa Kajang today is the communication has not been smooth due to the ego respective sectoral agencies, the lack of human resources in terms of Konjo language interpreter as well as the distance to the area of customs Ammatoa Kajang far enough.   Tujuan Penelitian ini adalah untuk mengetahui bagaimana Koordinasi antara Lembaga Adat dengan Pemerintah Daerah dalam hal pelestarian Hutan Adat di Kawasan Adat Ammatoa Kajang Kecamatan Kajang Kabupaten Bulukumba. Jenis penelitian adalah Kualitatif. Data tersebut dianalisis secara Deskriptif kualitatif. Hasil penelitian menunjukkan bahwa koordinasi anatara Pemerintah daerah dengan Lembaga adat dalam pelestarian hutan adat di kawasan adat Ammatoa Kajang Kabupaten Bulukumba berjalan dengan baik walaupun belum maksimal. Kendala koordinasi dalam pelestarian hutan adat Ammatoa Kajang saat ini yaitu komunikasi yang belum lancar disebabkan karena adanya ego sektoral masing-masing lembaga, kurangnya sumber daya manusia dalam hal penerjemah bahasa konjo serta jarak tempuh menuju kawasan adat Ammatoa Kajang yang cukup jauh.